Interpretasi Dan Ekspresi Penyaji Solis Violin Pada Pertunjukan Concerto In E Major, My Heart Will Go On, Dan Laila Canggung - Nasrullah, M.; Sidik, Hadaci; Awerman, Awerman; Hendri, Yon; Nurmalena, Nurmalena (Laga-Laga : Jurnal Seni Pertunjukan, 2025)
Performing musical compositions from various eras such as classical, modern, Malay, and popular, this violin solo recital presents a blend of interpretation, improvisation, and expressive performance using musical techniques that adhere to conventional principles.The initial preparation for the soloist before the performance includes technical exercises involving both the left and right hand techniques in solo violin playing. Each composition to be performed is analyzed in detail, especially in terms of form and structure. This process is essential for expressing each section of the composition appropriately and in accordance with the composer’s intent, particularly given that the compositions span different musical periods. This performance consists of several repertoires from different eras. The first repertoire originates from the Baroque period, spanning the 16th to 17th century, characterized by clear and structured patterns. This piece is titled Concerto in E Major No.1 "Spring" by composer Antonio Vivaldi, composed in 1725. The second repertoire is My Heart Will Go On, a popular music piece presented in a contemporary style. The third composition is Laila Canggung, created by Hamid and Amardi Raga, which is rooted in Malay cultural tradition and is expressed in accordance with Malay aesthetic values. The performer interprets and expresses each repertoire by applying various techniques such as arpeggio, trill, legato, slur, and slide, aiming to deliver a refined and complete performance.